Baseline assessment of knowledge, attitude, practice, and adherence toward antimicrobials among women living in two urban municipalities in Lalitpur district, Nepal - Nisha Jha; Sajala Kafle; Mili Joshi; Aakriti Pandey; Prakriti Koirala; Shital Bhandary; Pathiyil Ravi Shankar (PLoS ONE, 2025)
Introduction Antimicrobial resistance (AMR) is a significant problem in developing, low- and middle-income countries like Nepal. Community engagement can be an important means to address the problem. Knowledge, attitude, practice, and adherence of women regarding antibiotics and AMR was studied. Methods This baseline study was conducted in two urban municipalities of Lalitpur district as preparation for a larger intervention study (Mahalaxmi municipality will be the intervention and Godawari the comparison/control area). The study population was women belonging to the mother’s groups of 45 female community health volunteers (FCHVs) from each municipality. The study was done from September 2023 to January 2024. A total of 1207 individuals (580 in Mahalaxmi and 627 in Godawari) were involved. Data on demographics, knowledge, attitude, practice, and adherence was collected using a pre-validated structured questionnaire. Results The average age, educational status, monthly income, occupation, presence of respiratory disease, chronic diseases and communicable diseases were found to be not different among the two municipalities. Work experience, presence of respiratory disease and of health worker in the household was different in the baseline survey among the two locations. Knowledge was higher in Mahalaxmi municipality, but adherence was higher in Godawari municipality (p <0.0001). No significant difference was seen in attitude and practice scales. Knowledge, attitude, practice and adherence scores among different subgroups of respondents in the two municipalities were found to be significantly different for occupation (p <0.0001), and education (p <0.0001). The attitude scores were also significantly different according to presence/absence of respiratory disease in the household (p = 0.027). Conclusion At baseline the two study sites were broadly comparable in terms of participants’ demographic characteristics. There was higher knowledge and lower adherence in Mahalaxmi municipality. An educational intervention to improve KAP and adherence is required and will be conducted.